Pengaruh Corporate Governance Terhadap Kecurangan Laporan Keuangan - Feby Priswita; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to obtain empirical evidence and to analyze the effect of corporate governance’s mechanism such as managerial ownership, board of commissioners, audit committee, and institutional ownership effectiveness on likelihood of fraudulent financial reporting. This study uses secondary data from the company’s annual report for 2015-2017. The sampling method in this study used purposive sampling with a sample of 31 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The analysis used in this study is logistic regression analysis. The result showed that all of corporate governance’s mechanism such as managerial ownership, board of commissioners, audit committee, and institutional ownership have no significant effect on likelihood of fraudulent financial reporting.